Stagnation-point polydisperse spray flame ignition. Issue 5 (3rd September 2019) - Kats, Gershon; Greenberg, Jerrold Barry
Abstract : A theory of stagnation-point flow polydisperse spray flame ignition by an isothermal hot surface is presented for the first time. The configuration investigated consists of a mixture of fuel droplets and air flowing against an isothermal hot surface (such as a hot ignition probe). The polydisperse spray of droplets is modelled using the sectional approach. A single global chemical reaction is assumed for the case when ignition occurs. The mathematical analysis makes use of a small parameter that is exploited for an asymptotic approach. An analytical criterion for ignition is derived which includes effects of the flow field, the reactants and all the fuel spray-related parameters, including the initial size distribution of the spray's droplets. Numerical calculations disclose how the actual droplet size distribution impacts on the critical stagnation point temperature necessary to promote ignition. Additionally, the analytical estimates are compared with predictions of a numerical finite difference code with very satisfactory agreement.